Double Left Suprarenal Vein and its Clinical Implication - Khamanarong, Kimaporn; Sawatpanich, Tarinee; Chaichun, Amnart (Srinagarind Medical Journal, 2015)
Background and objective: Left suprarenal vein is a tributary of the left renal vein. It may present with an anatomical variant. It may be doubled, which surgeons must be aware of when performing adrenalectomies. The objective of this study was to report the double left suprarenal vein. Material and Method:This study comprised of 100 well embalmed cadavers. The abdominal cavity was opened by routine dissection procedure and double left suprarenal vein was traced. Result: Double left suprarenal vein was found in a 62 year-old- male cadaver, one receives the left inferior phrenic vein, while the other enters the adrenal tissue before joining, this common trunk drains into the left renal vein. Conclusion: This knowledge is critical to avoid left adrenalectomy procedures and left renal transplantation.